UPAYA MENINGKATKAN TANGGUNG JAWAB PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA MELALUI MODEL KOOPERATIF TIPE JIGSAW DI KELAS VIII A SMP N 2 LENDAH TAHUN PELAJARAN 2018/2019 - Wulandari, Nidya Ferry; Sutarna, Sutarna (Department of Mathematics Education , University of Jember, 2020)
The objective of this study was to improve students’ responsibility especially in math class with Jigsaw cooperative learning and to know the implementation of Jigsaw in math class. This study was a collaboration classroom action research. Kemmis & Mc. The Taggart model was used in this study. The subject of this study was students in eighth grade in SMP N 2 Lendah. The result of this study showed that there is an improvement in students’ responsibility in math class by using Jigsaw. Students played a role as an expert and they discussed specific topics. After that, they discussed again in a big group and shared what they got in a small group. There is 2 cycle because in the second cycle has achieved this study target. In last, there are no students who have low responsibility or below. Almost 70% of students have high responsibility and the rest have average responsibility.